2006
DOI: 10.2193/0022-541x(2006)70[931:nabsol]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nest and Brood Survival of Lesser Prairie-Chickens in West Central Kansas

Abstract: We evaluated the effect of habitat use and other sources of variation on survival of lesser prairie‐chicken (Tympanuchus pallidicinctus) and greater prairie‐chicken (Tympanuchus cupido) nests and broods. Daily nest and brood‐survival probabilities were a function of a quadratic time trend, and both declined as the season progressed. Daily nest survival was negatively associated with nest age, and daily brood survival was positively associated with brood age. Lastly, broods tended by adult females had higher da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 22 publications
5
68
1
Order By: Relevance
“…Timing of incubation and nest survival appear to be correlated; previous studies suggest that nests have a higher probability of survival if they are initiated earlier in the year [18], [31]. We hypothesize hot, dry conditions in the winter and spring affect the growth and composition of nest vegetation on our study area, which subsequently influence incubation and nest survival.…”
Section: Discussionmentioning
confidence: 63%
“…Timing of incubation and nest survival appear to be correlated; previous studies suggest that nests have a higher probability of survival if they are initiated earlier in the year [18], [31]. We hypothesize hot, dry conditions in the winter and spring affect the growth and composition of nest vegetation on our study area, which subsequently influence incubation and nest survival.…”
Section: Discussionmentioning
confidence: 63%
“…We did not separate first nest from renests in this analysis because of the low sample size of renests. Our microclimate candidate models were developed using information presented in Flanders-Wanner et al (2004), Fields et al (2006), Grisham et al (2013), Dunn and Milne (2014), and Hovick et al (2014) that suggested temperature and humidity as limiting factors for various aspects of Holarctic grouse reproductive ecology. We also included several exploratory models that included the proportion of extreme temperature and VPD measurements to assess whether extreme microclimate conditions influenced nest survival (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Age of brood hens was also an important indicator of brood survival. Survival probability to 60 days was 0.49 and 0.05 for broods reared by adults and sub-adults, respectively (Fields et al 2006).…”
Section: Nestingmentioning
confidence: 97%
“…Newell (1987) found 28% of subadult and 88% of adult hens re-nested, respectively. Fields et al (2006) observed the survival of Kansas prairie-chicken nests declined as the nest aged and as the nesting season progressed. They found survival probability of early-, mid-, and late-season nests was 0.77, 0.61, and 0.19, respectively.…”
Section: Nestingmentioning
confidence: 98%
See 1 more Smart Citation